SERVICES AT BANK BNI SISINGAMANGARAJA BRANCH: PELAYANAN PADA BANK BNI CABANG SISINGAMANGARAJA - Natalia Gulo, Desi (LPPM UPMI, 2024)
Service is an activity carried out by a person or group of people based on material factors through a certain system of procedures and methods in order to fulfill the interests of others according to their rights. Service at Bank BNI Sisingamangaraja branch always provides the best service to customers in order to improve the quality of the bank so that customers still always use the services of the bank, good service to customers is one of the important factors to improve the quality of the bank and to always maintain good relations between the bank and customers. The forms of service or services available at Bank BNI Sisingamangaraja branch are Customer Service, Teller Service, Bancassurance Service, Security Service. Based on the description above, the services available at Bank BNI Sisingamangaraja branch are services that help with every problem and complaint experienced by customers.